Population Genomic Analysis of Listeria monocytogenes From Food Reveals Substrate-Specific Genome Variation - Bechtel, Tyler D.; Gibbons, John G. (Frontiers in Microbiology, 2021)
Listeria monocytogenes is the major causative agent of the foodborne illness listeriosis. Listeriosis presents as flu-like symptoms in healthy individuals, and can be fatal for children, elderly, pregnant women, and immunocompromised individuals. Estimates suggest that L. monocytogenes results in ~1,600 illnesses and ~260 deaths annually in the United States. L. monocytogenes can survive and persist in a variety of harsh environments, including conditions encountered in production of fermented dairy products such as cheese. For instance, microbial growth is often limited in soft cheese fermentation because of harsh pH, water content, and salt concentrations. However, L. monocytogenes has caused a number of deadly listeriosis outbreaks through the contamination of cheese. The purpose of this study was to understand if genetically distinct populations of L. monocytogenes are associated with particular foods, including cheese and dairy. To address this goal, we analyzed the population genetic structure of 504 L. monocytogenes strains isolated from food with publicly available genome assemblies. We identified 10 genetically distinct populations spanning L. monocytogenes lineages 1, II, and III and serotypes 1/2a, 1/2b, 1/2c, 4b, and 4c. We observed an overrepresentation of isolates from specific populations with cheese (population 2), fruit/vegetable (population 2), seafood (populations 5, 8 and 9) and meat (population 10). We used the Large Scale Blast Score Ratio pipeline and Roary to identify genes unique to population 1 and population 2 in comparison with all other populations, and screened for the presence of antimicrobial resistance genes and virulence genes across all isolates. We identified >40 genes that were present at high frequency in population 1 and population 2 and absent in most other isolates. Many of these genes encoded for transcription factors, and cell surface anchored proteins. Additionally, we found that the virulence genes aut and ami were entirely or partially deleted in population 2. These results indicate that some L. monocytogenes populations may exhibit associations with particular foods, including cheese, and that gene content may contribute to this pattern.